Cuidados com o potro órfão: revisão de literatura - Silva, Elisa Sant’Anna Monteiro [UNESP]; Scalco, Elisa Maciel [UNESP]; Lamberti, Marcela [UNESP]; Surian, César Rodrigo de Souza [UNESP]; Puoli-Filho, José Nicolau Próspero [UNESP] (My University, 2013)
Raising orphaned foals is a great challenge, as it requires intense monitoring and frequent care. However, with an appropriate handling, it is possible to raise a healthy orphaned foal in a similar manner to those raised by their own mothers. In addition to providing feeding and health care, other factors should receive equal attention, such as the foals’ behavior and social contact with other animals of the same species. Thus, this article aims to review the main factors involved with the raising of orphan foals from birth to weaning.

A criação de potros órfãos é um grande desafio, pois exige monitoração intensa e cuidados freqüentes. No entanto, com o manejo adequado, é possível criar um órfão de forma saudável e similar aos animais criados por suas próprias mães. Além do fornecimento de alimentação e cuidados com saúde, outros fatores devem receber igual atenção, como a observação do comportamento destes potros e socialização com outros animais da mesma espécie. Desta forma, o presente trabalho tem como objetivo revisar os principais fatores envolvidos na criação de potros órfãos, desde o nascimento até o desmame.
Care of the orphan foal: literature review
Keywords: Foals; Orphan; Colostrum; Feeding; Behavior; Potros; Órfãos; Colostro; Alimentação; Comportamento